(untitled) (Journal of Nepal Geological Society, 2010)
Mafic intrusive within Neoproterozoic carbonates of Miri-Buxa Group in the Panging area of the Arunachal Lesser Himalaya, NE India has been reported for the first time. These mafic rocks have affinity to subalkaline-Mg-tholeiites and identified as low-Ti gabbro. Geochemically they are characterized by enrichment in LILE and LREE, depleted in HFSE with minor REE fractionated nature [(La/Yb)N = 2.70-3.29)] and positive Eu anomalies (Eu/Eu* = 1.00-1.30). These rocks have the influence of a within plate signature which were intruded in a continental rift tectonic environment. Petrogenetic modelings of [Mg]-[Fe] and REE suggest these mafic rocks probably derived from enriched mantle source similar to komatiitic composition at moderate to higher degree (35% - 50%) of partial melt. Based on the present reported microfossils viz. Rivularia haematites and Filamentus cyanobacteria in the chert lenses of the Buxa Dolomite from the Panging area, it is suggested that the gabbroic intrusion might have been taken place during Late Neoproterozoic which is probably close to the Precambrian–Cambrian boundary.